2019
DOI: 10.1177/2055116919835081
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma and hepatic myelolipoma incarcerated in a peritoneopericardial diaphragmatic hernia with pulmonary metastasis and carcinomatosis in a cat

Abstract: Case summary A 14-year-old female neutered Persian-cross cat was presented with a 1 week history of anorexia and lethargy. On physical examination, marked tachypnoea and dyspnoea were evident. Radiographs of the thorax revealed a globoid-shaped cardiac silhouette with heterogeneous opacity consistent with a peritoneopericardial diaphragmatic hernia (PPDH), pulmonary nodules compatible with metastasis, seven sternal segments and a small liver in the cranial abdomen with loss of serosal detail. On e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 11 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Hematological examinations in cats affected by PPDH may present subtle changes (Barge et al, 2019) or may not show changes (Banz & Gottfried, 2010;Liptak et al, 2002). Therefore, even in the presence of a blood cell count and serum chemistry profile within normal range or with subtle changes, as in this report, it is possible to have PPDH.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Hematological examinations in cats affected by PPDH may present subtle changes (Barge et al, 2019) or may not show changes (Banz & Gottfried, 2010;Liptak et al, 2002). Therefore, even in the presence of a blood cell count and serum chemistry profile within normal range or with subtle changes, as in this report, it is possible to have PPDH.…”
Section: Discussionmentioning
confidence: 68%
“…The cat did not show clinical signs associated with the presence of PPDH, such as changes in the gastrointestinal or cardiorespiratory system (Barge et al, 2019;Barrett & Kittrell, 1966;Liptak et al, 2002), being observed only in apathy, weight loss, and lack of appetite. As in this report, some animals can be diagnosed as middle-aged or older (MacPhail, 2014), may be asymptomatic, and Then, a small incision was made in the pericardium to remove its adhesion to the diaphragm.…”
Section: Discussionmentioning
confidence: 88%
“…The cat did not show clinical signs associated with the presence of PPDH, such as changes in the gastrointestinal or cardiorespiratory system ( Barge et al, 2019 ; Barrett & Kittrell, 1966 ; Liptak et al, 2002 ), being observed only in apathy, weight loss, and lack of appetite. As in this report, some animals can be diagnosed as middle-aged or older ( MacPhail, 2014 ), may be asymptomatic, and may not even reveal pathological changes in herniated or thoracic organs ( Cunha et al, 2000 ; Hunt & Johnson, 2007 ).…”
Section: Discussionmentioning
confidence: 93%
“…It has also been reported that herniation of the liver is associated with a poor prognosis in fetal congenital diaphragmatic hernia in human medicine, suggesting compression of the lung by the herniated liver, and increased size of defect in the diaphragm and disturbed regulation of liver growth [ 13 ]. Studies have also described malignant neoplasia with or without hepatic myelolipoma in old cats with PPDH [ 14 15 ]. Thus, the prolonged enclosure of the hepatic parenchyma in a PPDH without surgical treatment can increase the risk of transformation and malignant changes because of vascular and lymphatic congestion and chronic hypoxia of hepatic tissue [ 14 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also described malignant neoplasia with or without hepatic myelolipoma in old cats with PPDH [ 14 15 ]. Thus, the prolonged enclosure of the hepatic parenchyma in a PPDH without surgical treatment can increase the risk of transformation and malignant changes because of vascular and lymphatic congestion and chronic hypoxia of hepatic tissue [ 14 15 ]. The development of myelolipomas may be associated with the presence of foci of tumor necrosis in human medicine [ 16 ].…”
Section: Discussionmentioning
confidence: 99%